2014
DOI: 10.1039/c4fo00029c
|View full text |Cite
|
Sign up to set email alerts
|

High levels of Bifidobacteria are associated with increased levels of anthocyanin microbial metabolites: a randomized clinical trial

Abstract: The health benefits associated with the consumption of polyphenol-rich foods have been studied in depth, however, the full mechanism of action remains unknown. One of the proposed mechanisms is through microbiota interaction. In the present study, we aimed to explore the relationship between changes in fecal microbiota and changes in urinary phenolic metabolites after wine interventions. Nine participants followed a randomized, crossover, controlled interventional trial. After the washout period, they received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 47 publications
3
78
0
Order By: Relevance
“…and Lactobacillus spp., possibly due to their capacity to degrade phenolic compounds such as anthocyanin metabolites. 42 Other studies by Vendrame et al 43 and Hidalgo et al 44 also indicated that anthocyanins seemed to increase the number of Bifidobacterium spp. and Lactobacillus spp.…”
Section: Food and Function Papermentioning
confidence: 97%
“…and Lactobacillus spp., possibly due to their capacity to degrade phenolic compounds such as anthocyanin metabolites. 42 Other studies by Vendrame et al 43 and Hidalgo et al 44 also indicated that anthocyanins seemed to increase the number of Bifidobacterium spp. and Lactobacillus spp.…”
Section: Food and Function Papermentioning
confidence: 97%
“…A cross-sectional study, which included 178 elderly subjects, observed that habitual diet-driven microbiota alterations were associated with health status, including measures of frailty and inflammation (132), whereas in a study that was limited to 15 women, a 2-mo dietary intervention was associated with changes in Gammaproteobacteria and Erysipelotrichi microbial communities (133). In a recent small RCT ( n = 9), high amounts of Bifidobacteria were associated with increased amounts of flavonoid microbial metabolites after polyphenol-rich wine intake (134). Several recent animal studies observed profound effects in the gut microbial community structure after intake of flavonoid-rich foods although it is possible that there are differences in the permeability of microbiome-derived metabolites between rodents and humans.…”
Section: Etiology Of the Heterogeneity In Flavonoid Admementioning
confidence: 99%
“…[18]; (2) suppressing the adhesion of gut pathogens to human gut cells [19]; (3) enhancing natural killer cell activity and cytokine secretion [20]. In older adults (40-50 years old), a higher urinary concentration of phenolic metabolites of anthocyanin such as syringic acid, p-coumaric acid, 4-hydroxybenzoic acid, and homovanillic acid was associated with higher bifidobacteria level (> 4.47 vs. < 1.18 log 10 copies per g faeces) [17]. Research into the bioavailability and metabolism of (poly)phenols, has so far been mostly limited to young adults [21][22][23][24][25][26], and inter-individual factors likely to impact on the outcome measures have rarely been studied in depth [27][28][29][30][31][32][33].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Recently, the International Scientific Association for Probiotics and Prebiotic expanded the definition of the prebiotics to include (poly)phenolics as they are selectively metabolised by gut microbiota and release microbial bioactive molecules (including phenolic acids) that may confer local and systematic health benefits [15]. The interactions between the gut microbiota and (poly)phenols have been described in two ways: (1) some (poly)phenols metabolites have the capability to promote and/or inhibit the growth certain bacteria [16] and (2) the gut microbiota contributes to the production of small potentially bioactive molecules including phenolic acids [17]. (Poly)phenolics may have protective effects in the gastrointestinal tract by: (1) inhibiting the growth of pathogenic species, e.g.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%